Environmental Degradation and Interfaith Efforts: A Contemporary Discourse of Islam and Hinduism (Al-Qamar, 2022)
Today, Environmental degradation is an alarming issue our only living planet Earth is facing on a global level. It is basically a process of destruction of a potentially renewable resource such as water, forest, animals, air, and wildlife etc. It can be seen in the form of lost living forms due to the disturbance in the ecosystem of planet Earth. The recent developments in the human worldview and civilization are the main reasons for such environmental degradation. In this present scenario of environmental degradation, Islam and Hinduism provides a holistic approach for equilibrium of Earth and its ecosystem. In this regard, the contemporary discourse is more relevant to control human’s anthropogenic activities. In their interfaith efforts for the protection of environment, contemporary eco-scholars of Islam and Hinduism have revised the ecological worldview, the place and position of mankind in the hierarchy of cosmos, and the sacred quality of environment in the mind of modern man. This interfaith research presents a comparative analysis of the eco-religious understandings of contemporary thinkers of both faiths to sustain Man-Environment relationship in 21st century. Through discussion of their eco-religious views, this paper motivates human beings to use natural resources of Earth in balance way and ensure the peaceful co-existence of all species.
Keywords: Environmental degradation; nthropocosmic; peaceful co-existence; interfaith effort; Hinduism; Islam; Man; Earth